GEOCHEMISTRY AND FORMATION CONDITIONS OF RARE-METAL GRANITES WITH VARIOUS FLUORINE-BEARING MINERALS (FLUORITE, TOPAZ, AND CRYOLITE) - Antipin V.S.; Savina E.A.; Mitichkin M.A. (My University, 2006)
A comparative geochemical study of rare-metal granitoids with various fluorine-bearing minerals (fluorite, topaz, and cryolite) was carried out. It was shown that these rocks correspond to both plumasitic and agpaitic geochemical types. The fluorite-, topaz-, and cryolite-bearing granites of these geochemical types are distinctly different in geochemical parameters and the character of magmatic evolution. These differences are related to the composition of initial magmas and their sources. Rare-metal granitoids with fluorine-bearing minerals compose small massifs, stocks, and dike swarms. Their formation is independent of the composition and age of the country rocks or geologic structures where they occur. © Pleiades Publishing, Inc. 2006.